Applied radiation physics techniques for diagnostic evaluation of the plasma wind and thermal protection system critical parameters in aerospace re-entry. (January 2020) - De Cesare, M.; Savino, L.; Ceglia, G.; Alfano, D.; Di Carolo, F.; French, A.D.; Rapagnani, D.; Gravina, S.; Cipullo, A.; Del Vecchio, A.; Di Leva, A.; D'Onofrio, A.; et al.
Abstract: The reentry conditions endured by a vehicle entering the atmosphere from an Earth orbit or from an interplanetary trajectory are the most critical phases for materials used as Thermal Protection Systems (TPSs), since the spacecraft surfaces have to withstand extremely high heat fluxes and loads due to the hot plasmas generated downstream of the high energy shock waves due to the extreme deceleration. The gases are highly excited and heated to values up to 10000 K immediately downstream of the shock waves. The TPS surfaces are then heated by these gases through convection and radiation, producing very high wall heat fluxes and associated temperatures, which can produce TPS surface temperatures of up to 2300 K. Passive and active TPSs are employed to protect the inner cold structures of the spacecraft which are made from aluminium or metallic alloys. Passive TPS are classified as reusable or single use (ablative) materials. Facilities such as plasma wind tunnels are used to experimentally reproduce the atmospheric reentry of such vehicles. Their use allows the testing and qualification of the TPS which is subjected to thermal and mechanical stresses induced by the hypersonic jet in spite of the unavoidable intrinsic limitations when the complex flight physics phenomena are reproduced in ground test facilities. One of the most complex issues, associated with aerospace safety during a hypersonic Plasma Wind Tunnel test campaign is to measure the free jet temperature and monitor the high heat fluxes generated by the hot plasma, the correlated TPS surface temperatures, and the erosion rate (i.e., recession rate) affecting the behavior of materials representative of space vehicle subcomponents. The purpose of the present work is to review the diagnostic methodologies used in hypersonic test facilities associated with the working principles, the development, the potential and the limitations of arc jet plasma wind tunnels for the evaluation of the aforementioned critical parameters. At the same time, this review aims to illustrate the most advanced and sensitive non-intrusive diagnostics for the determination of the free jet temperature and its oxygen composition by means of spontaneous Optical Emission Spectroscopy (OES) and Laser Induced Fluorescence (LIF) respectively, and for the determination of the TPS temperature and erosion rate using free emissivity Dual Color Infrared Thermography (DCIT) and on Surface Layer Implantation (SLI) of radioactive tracers techniques.